THE EFFECTIVENESS OF WORD SEARCH PUZZLE GAME AS MEDIA FOR TEACHING VOCABULARY - Wahyudi, Mohammad Arief (ELP (Journal of English Language Pedagogy), 2024)
The insufficient vocabulary of students often leads to their reluctance in applying English language skills. To address this issue and encourage active usage of English, it is crucial to focus on vocabulary development through effective learning practices. In this context, the researcher sought a solution to enhance writing skills and promote a deeper understanding of word meanings. The chosen approach involved incorporating an engaging and enjoyable medium, namely the Puzzle game, as a means of facilitating vocabulary growth. The Puzzle game, specifically the Word Search Puzzle, was selected as it not only serves as a game but also captures students' interest by sparking curiosity about hidden words. In a Word Search Puzzle game, players search for concealed words in provided boxes, guided by word clues. These words may be arranged vertically, horizontally, or diagonally within the grid. The study involves a sample of 20 students selected from the entire population. Utilizing SPSS 22 for calculations, the results indicate statistical significance, leading to the conclusion that the Word Search Puzzle game is effective in enhancing vocabulary. This finding underscores the proven efficacy of the Word Search Puzzle game as a learning medium, demonstrating its capacity to augment students' vocabularies. Consequently, teachers can consider integrating this method into their teaching practices to facilitate effective vocabulary instruction.